Microwave Activation Of Sol-Gel Spin Coated Magnesium Doped Gallium Nitride Thin Films - Sekaran, Vinoshni; Amin, NurFahana Mohd; Sha, Shiong Ng (2017)
In this paper, microwave (MW) activation of sol-gel spin coated magnesium (Mg) doped gallium nitride (GaN) thin films grown on sapphire (001) substrates were reported. The attention was paid to the effects of MW activation power on structural and optical properties of these p-type GaN films. X-ray diffraction results indicate that the Mg-doped GaN thin films exhibit hexagonal wurtzite structure with (002) preferential orientation. Besides, the Mg-doped GaN thin film activated at 450 W has the highest dislocation density, 6, implies that it has the largest amount of nitrogen vacancies compared to all the other samples, and consequently the poorest crystalline quality as proved by the drastic decrease in intensities of the XRD peaks of the film. Since nitrogen vacancies are favourably formed only upon the removal of hydrogen from p-type GaN, it can be deduced that the activation process of Mg dopants is most efficient at 450 W. Tensile strain along caxis of the film activated at 450 W further validates this statement. Raman scattering measurements showed the presence of E2(high) mode of hexagonal GaN in all the Mg-doped GaN thin films, except in film activated at MW power of 450 W where the E2(high) mode peak is extremely weak and broad. The smallest crystall ite size of the Mg-doped GaN thin film activated at MW power of 450 W leads to optical phonon confinement, resulting in broadening of E2(high) mode. In summary, 450 W is the best power for the activation process of Mg dopant, but yet it is not the most ideal MW power because it deteriorates the crystalline qualit y of the films.